(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
The objective of this research is to study the effect of sintering temperature on the mechanical properties and micro-strain of yttria tetragonal zirconia polycrystalls (Y-TZP) nanostructure. Where green disk formed by uniaxially press, sintered at (1500 – 1550 – 1600⁰C) in air for 2hr then polished to mirror shape for fracture toughness and micro-hardness measurement by Vickers indenter at (60 kg to 100gm) loads. Atomic force microscopy (AFM) technique was use to measure the change in grain size and shape of the samples, X-ray diffraction (XRD) evaluated to identify the phases and to measure the micro-strain of the samples. The Results show that increasing sintering temperature will increase the grain size with increasing the average of micro-strain. Tetragonal phase is the prevailing phase with small amount of cubic phase and the amount of monoclinic phase was under detection limite after sintering but there is increas in lattice dimension according to micro-strain calculation and grinding process produce micro-strain. With increasing the sintering temperature micro-hardness and fracture toughness will increas.